Phytochemistry and Biological Evaluation of Cyperus rotundus and Typha latifolia from Lugari Region of Western Kenya - Wangila TP (Chemistry and Biochemistry: Research Progress Vol. 4, 2025)
In Western parts of Kenya, Cyperus rotundus and Typha latifolia are used in the treatment of infectious diseases. Phytochemical compounds and antimicrobial activity of Cyperus rotundus and Typha latifolia reeds plants from Western Kenya, which are used in the management and treatment of various ailments, were determined. Samples were collected from the Lugari region of Western Kenya. Solvent extraction using ethyl acetate on powdered samples was done. Phytochemical tests were conducted on the extracts of Cyperus papyrus and Typha latifolia using standard methods. Five phytochemicals were tested positively in C. rotundus and T. latifolia these include Tannins, Steroids, Saponin, Alkaloid and Glycoside. Flavonoid was tested negatively in C. rotundus and T. latifolia. The methanol extracts of C. rotundus and T. latifolia were subjected to antibacterial assay on Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, Bacillus subtilis and Candida albicans. Disc agar (cup-plate) diffusion method was adopted for antimicrobial activity test against gram-positive and gram-negative bacteria. The maximum antimicrobial activities were observed at 100% concentration than at 10% of methanol extracts of C. rotundus and T. latifolia and no antimicrobial activities were observed at 1%. From this study’s findings, T. latifolia and C. rotundus extracts can be used as good antibacterial agents. C. rotundus can be used against Bacillus substilis unlike the standard antibiotics and T. latifolia. Further research for isolation and characterization of compounds responsible for the observed antimicrobial activity. Here is needed to carry out the antifungal and antioxidant activities of T. latifolia and C. rotundus.